Teacher's perspectives of a transformative history curriculum in Lesotho high schools - Lesaoana, Matseliso (University of the Free State, 2018)
The study was undertaken with the aim to determine teachers’ perspectives of a transformative History curriculum in Lesotho high schools. The interest was brought by the realisation that the Lesotho Government through its Ministry of Education and Training published the revised curriculum in 2008 and implementation started in 2013. The review of literature suggests that curriculum change would also mean a shift in pedagogy. Hence the interest to establish the understanding that teachers have and if the methods they used addressed the requirements of the revised curriculum. The Lesotho Curriculum and Assessment Policy Framework displays characteristics of transformative curriculum, hence the phenomenon of investigation in this study was transformative learning. Literature review suggests that transformative learning is a learning theory that challenges students’ thinking and highlights the importance of cultivating a process of critical reflection. Transformative learning places emphasis on students to become actively engaged in new awareness of social justice. Consequently this study was guided by critical pedagogy, a philosophy of education that applies concepts from critical theory. Critical pedagogy is praxis in nature and in a classroom situation it requires those teachers who employ it to act as model for democratic process and to offer empowering education. Critical pedagogy therefore assisted the researcher to determine the meaning attached to and how effective teachers were implementing a transformative History curriculum. Critical pedagogy is further aligned to constructivism and interpretive paradigm in that knowledge is a social construct. Essentially this study employed qualitative methodology because of its interpretive nature. Qualitative methods namely interviews and observations were used for data collection and they allowed for conversation and interpretation of the actions and feelings of History teachers in three Lesotho high schools. Document analysis was another qualitative method used for data collection and it offered an opportunity to interpret documents, which among others included the History curriculum and lesson plans. A Coding system was used to analyse data where themes were created to facilitate for interpretation of the findings. Findings from empirical research pointed to lack of sufficient knowledge and skills of a transformative curriculum. Lack of understanding resulted in ineffective implementation because teaching did not address skills and was not in a manner that addressed a transformative History curriculum. The implications and conclusions drawn from the results pointed to a need for a concerted effort by policy makers and the leadership of schools to provide the necessary support to teachers for the effective implementation of a transformative History curriculum in Lesotho high schools. The study is however limited in that the sample was selected using non-probability sampling therefore the sample was small and thus the results might not be generalised. However the credibility, reliability, validity and transferability of the results can be found in the use of purposive sampling. This type of sampling seeks saturation whereby participants were selected to specifically understand and learn from them. The rigour of qualitative research through triangulation methods also allowed for confirmation, as data collected corroborated and complemented each other.
Thesis (Ph.D. (Curriculum Studies))--University of the Free State, 2018
Keywords: Transformative learning; Critical pedagogy; Praxis; Curriculum; Curriculum change